MODEL BIMBINGAN KELOMPOK BERBASIS NILAI NENGAH NYAMPUR DALAM FALSAFAH HIDUP MASYARAKAT LAMPUNG UNTUK MENINGKATKAN PENYESUAIAN DIRI SISWA - Rosidah, Ainur; Nurfaizal, Nurfaizal; Fitria, Nita (JURNAL FOKUS KONSELING, 2015)
AbstractÂ Self adjusment being a major capital hearts facing the challenges of life are fluctuating. Self adjustment problems in this research will be enhanced through the provision of group counseling services based the value